Investigation on roles and task of construction managers in developing construction management competency: perspectives from Malaysian construction industry / Siti Sarah Mat Isa, Wan Norizan Wan and Farhan Md. Dahlan - Mat Isa, Siti Sarah; Wan, Wan Norizan; Md. Dahlan, Farhan (2012)
Construction managers form an integral part of the industry' workforce. Performing at the sharp end of the construction project, they contribute significantly to the success of any construction project. Construction managers in Malaysian construction industry are faced with a situation whereby the fundamental roles and tasks they perform are witnessing a gradual shift in focus. In order to maintain their professional competency, practicing in construction project adapt to this changing industry environment by relying on knowledge and skills acquired through education and training. This paper discussed the need to investigate the roles and tasks performed at the job, taking into account the personal, situational and organisational variables which can impact the construction management competency. This research presents a study that focuses on the development of construction managers and how they maintain their professional competency in a changing construction business environment. The paper first sets out the areas of roles and tasks required for construction management for today's construction managers. This implies that an improved approach of establishing the general roles and tasks that are perceived as essential for developing construction management competency in the construction industry. It emerged that in the main, notwithstanding the size of construction organisation employing them Malaysian construction managers have roles and tasks which are fundamentally common.